Adhesive small bowel obstruction after laparotomy during infancy. Issue 3 (15th December 2015) - Fredriksson, F; Christofferson, R H; Lilja, H E
Abstract: Background: Intra-abdominal adhesions can cause adhesive small bowel obstruction, chronic abdominal pain and female infertility. Reports on long-term outcomes following laparotomy during infancy are scarce. The aims of this study were to investigate the incidence of and risk factors for long-term adhesive small bowel obstruction and associated morbidity after laparotomy during infancy. Methods: Infants who underwent laparotomy between 1976 and 2011 were identified. Data were extracted from medical records and a questionnaire was sent to the patients. Results: Some 898 of 1185 eligible patients were included, with a median follow-up time of 14·7 (range 0·0–36·0) years. Median age at first laparotomy was 6 (range 1·0–365·0) days. There were 113 patients (12·6 per cent) with adhesive small bowel obstruction who underwent relaparotomy, 79 (69·9 per cent) occurring during the first 2 years after the initial laparotomy. The highest incidence of small bowel obstruction was found in patients with Hirschsprung's disease (19 of 65, 29 per cent), malrotation (13 of 45, 29 per cent), intestinal atresia (11 of 40, 28 per cent) and necrotizing enterocolitis (16 of 64, 25 per cent). Lengthy duration of surgery (hazard ratio (HR) 1·25, 95 per cent c.i. 1·07 to 1·45), stoma formation (HR 1·72, 1·15 to 2·56) and postoperative complications (HR 1·81, 1·12 to 2·92) were independent risk factors. Chronic abdominal pain was reported in 180 (24·0 per cent) of 750 patients, and 17 (13·8 per cent) of 123 women reported infertility. Conclusion: The incidence of adhesive small bowel obstruction after laparotomy in infants is high. Abstract : High incidence